Identification of Challenges in the Development of Early Childhood Education Institution in Kendari, Southeast Sulawesi - Abubakar, Sitti Rahmaniar; Salwiah, Salwiah; Pabunga, Dorce Banne; M, Mansyur (Universitas Negeri Semarang, 2016)
Identification of challenges in the development of early childhood education institution in Kendari, Southeast Sulawesi. The problem in this research is: what are the challenges in the development of early childhood education in Kendari?This research aims to identify the challenges in the development of early childhood education in the city of Kendari. This type of research is qualitative research with descriptive analysis techniques.The data were collected using documentation and interview technique. The results showed: 1) limited understanding of parents about the importance of education for early childhood, 2) academic qualification of early childhood educators are still insufficient because there is still some educators who high-school graduates, 3) most teachers do not have adequate competence regarding their inappropriate educational background, have not obtained training-related concepts and practical science about early childhood education.It is suggested that (1) a high commitment be requiredfrom Government, community leaders and stakeholders to conduct socialization in society and parents about the importance of education for early childhood, 2) educators are facilitated to attend further education at an accredited study programs in early childhood education, and 3) educators are encouraged to attend various trainings, workshops and other scientific activities in order to increase the competence of educational progress, especially education for early childhood.